Physiology of deep closed circuit rebreather mixed gas diving: vascular gas emboli and biological changes during a week-long liveaboard safari - Balestra, Costantino; Lévêque, Clément; Mrakic-Sposta, Simona; Vezzoli, Alessandra; Wauthy, Pierre; Germonpré, Peter; Tillmans, Frauke; Guerrero, François; Lafère, Pierre (Frontiers in Physiology, 2024)
Diving decompression theory hypothesizes inflammatory processes as a source of micronuclei which could increase related risks. Therefore, we tested 10 healthy, male divers. They performed 6-8 dives with a maximum of two dives per day at depths ranging from 21 to 122 msw with CCR mixed gas diving. Post-dive VGE were counted by echocardiography. Saliva and urine samples were taken before and after each dive to evaluate inflammation: ROS production, lipid peroxidation (8-iso-PGF2), DNA damage (8-OH-dG), cytokines (TNF-a, IL-6, and neopterin). VGE exhibits a progressive reduction followed by an increase (p<0.0001) which parallels inflammation responses. Indeed, ROS, 8-iso-PGF2, IL-6 and neopterin increases from 0.19 ± 0.02 to 1.13 ± 0.09 μmol.min-1 (p<0.001); 199.8 ± 55.9 to 632.7 ± 73.3 ng.mg-1 creatinine (p<0.0001); 2.35 ± 0.54 to 19.5 ± 2.96 pg.ml-1 (p<0.001); and 93.7 ± 11.2 to 299 ± 25.9 μmol•mol-1 creatinine (p=0.005), respectively. The variation after each dive was held constant around 158.3 ± 6.9% (p = 0.021); 151.4 ± 5.7% (p <0.0001); 176.3 ± 11.9% (p<0.0001); and 160.1 ± 5.6% (p<0.001), respectively. When oxyinflammation reaches a certain level, it exceeds hormetic coping mechanisms allowing second-generation micronuclei substantiated by an increase of VGE after an initial continuous decrease consistent with a depletion of "first generation" pre-existing micronuclei.